Literature Review of Panchvalkaladya Churna & Kashaya in the Management of Non-Healing Wound - Balara, Rajkumar; Gupta, Rajesh Kumar ,; Srivastava, Sanjay (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is a science of life and is presumed when the origin of life on this earth is mentioned in Samhita. In many references or ancient books miracle of Ayurveda is described. This miracle is proven in the form of enhanced quality for longer life. Moreover, Ayurveda provides new life by eradicating severe diseases. Ayurveda is broadly described in eight parts. Knowledge Vrana is one of them that are governed by human from the dawn of civilization. Human beings have been vulnerable to harm since beginning, prompting them to consider healing from an early stage of development. The injury from various causes lead to Vrana under many circumstances (wound). Vrana is an awful and alarming condition that can influence individuals of all ages. At the same time, wound recuperating is quite difficult for all. Thus, mending of wounds is essential. Many elements influence wound mending. Hardship-free aseptic nature of the injury is the first and most significant element to consider for its mending. Afterward the arrangement of a solid injury bed which brings about mending from now on.